Engaging with Flows: Embodied Cognition in Water Provision - Edwin Rap (Water, 2019)
This article provides an ethnographic example of a practice-based approach to water governance. It presents the situated case study of a canalero (canal operator) in the everyday water distribution of an irrigation system in Western Mexico. The canalero represents the low-ranked field operators at the frontline of many water provision organizations around the world, thereby providing a wider relevance to this case study. In spite of different waves of modernization that aimed to reduce ‘the human element’ and control water flows from a distance, canaleros still operate the manually adjustable gates and intakes in many medium and large open canal irrigation systems. Through a precise documentation of the daily routines of administering water, money, and data flows, anticipating shortages and mediating between conflicting demands, we conceptualize their semi-autonomous field of competent action. In contrast to a rule-based or normative approach to water governance, we will argue that the canaleros’ cognition and competencies in mediating multiple resource flows are embodied and situated in specific social, technical and spatial arrangements for water provision. However, this field of professional competence is not clearly delineated and gets regularly contested in practice. The water operators deal with these ‘problems of control’, by drawing on their situational knowledge and embodied cognition acquired on-the-job. This case study outlines a framework for a practice-based and decentered study of water governance, focused on cognitive processes in water provision arrangements.